DETERMINATION OF THE EFFECTS OF LEVOFLOXACIN ON GENTAMICIN INDUCED NEPHROTOXICITY IN RABBITS: A COMPARATIVE STUDY: Levofloxacin and Gentamicin Induced Nephrotoxicity - Naeem, Uzma; Jamal, Shahid; Waheed, Akbar (Pakistan Armed Forces Medical Journal, 2015)
Objective: To determine the effects of levofloxacin on gentamicin induced nephrotoxicity in rabbits.Study Design: Comparative experimental study.Place and Duration of Study: The animal house of Army Medical College, Rawalpindi, and the pathology department of Army Medical College, Rawalpindi, from July 2009 to January 2010.Material and Methods: The effects of levofloxacin on gentamicin-induced nephrotoxicity were evaluated in rabbits. Twenty four rabbits were used in this study which were randomly divided into four groups (n= 6 in each group). Six animals were injected for 15 days with saline (NaCl; 0.9%), six with gentamicin alone at doses of 20 mg/kg of body weight/12 h (intramuscularly), six with combination of gentamicin (20 mg/kg/12 h) with low therapeutic doses of levofloxacin (30 mg/kg/24 h) and the last six were treated with gentamicin and high therapeutic doses of levofloxacin (50 mg/kg/24 h). Levofloxacin was given by intraperitoneal route.Results: Gentamicin induced nephrotoxicity was evaluated by histopathological and serum analysis. The extent of nephrotoxicity was significantly increased when gentamicin was given in combination with levofloxacin both in low and high doses.Conclusion: Levofloxacin enhances gentamicin induced nephrotoxicity and extent of this nephrotoxicity increased with increasing dose of levofloxacin.